2020
DOI: 10.1186/s12967-020-02271-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic PPARγ is a marker of poor prognosis in patients with Cox-1 negative primary breast cancers

Abstract: Background: The aim of this study was to investigate the expression of the nuclear receptor PPARγ, together with that of the cyclooxygenases Cox-1 and Cox-2, in breast cancer (BC) tissues and to correlate the data with several clinicobiological parameters including patient survival. Methods: In a well characterized cohort of 308 primary BC, PPARγ, Cox-1 and Cox-2 cytoplasmic and nuclear expression were evaluated by immunohistochemistry. Correlations with clinicopathological and aggressiveness features were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
1
24
0
1
Order By: Relevance
“…These findings would explain the opposite effect on survival when PPARγ is detected in the nucleus or in the cytoplasm: Nuclear expressed PPARγ is a prognostically favorable factor in overall survival, but detection in the cytoplasm is a prognostically unfavorable factor in disease-free survival and shows an unfavorable trend in overall survival. Shao et al [ 94 ] described an unfavorable overall survival in breast cancer patients showing a high-expression level of PPARγ in cytoplasma. In some tumor entities, a positive prognostic influence of nuclear PPARγ expression on the survival of tumor patients has already been identified, but a difference between expression localization and relation to different patient outcome was not described [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings would explain the opposite effect on survival when PPARγ is detected in the nucleus or in the cytoplasm: Nuclear expressed PPARγ is a prognostically favorable factor in overall survival, but detection in the cytoplasm is a prognostically unfavorable factor in disease-free survival and shows an unfavorable trend in overall survival. Shao et al [ 94 ] described an unfavorable overall survival in breast cancer patients showing a high-expression level of PPARγ in cytoplasma. In some tumor entities, a positive prognostic influence of nuclear PPARγ expression on the survival of tumor patients has already been identified, but a difference between expression localization and relation to different patient outcome was not described [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in patients with breast and prostate cancer, PPARγ is a marker of better prognosis and is associated with better survival (161)(162)(163). Importantly, one study reports that cytoplasmic PPARγ expression appeared as an independent marker of poor prognosis in primary breast cancers (198). TCGA analysis proposed PPARγ as a favorable prognostic marker for renal and urothelial cancers ( Table 1).…”
Section: Lipid-related Transcription Factor Alterations As Biomarkersmentioning
confidence: 99%
“…prognostically unfavorable factor in disease-free and OS in various carcinoma, including in breast cancer [46,47]. These results indicate that the functional form of PPARγ may exert a potential protective role in breast cancer patients.…”
Section: Pparγ As a Molecular Target For Breast Cancer Therapymentioning
confidence: 71%
“…However, the prognostic significance of PPARγ in breast cancer is clearly different depending on its subcellular localization. Recent data have shown that nuclear expression of PPARγ is associated with longer OS, whereas detection in the cytoplasm is a prognostically unfavorable factor in disease-free and OS in various carcinoma, including in breast cancer [ 46 , 47 ]. These results indicate that the functional form of PPARγ may exert a potential protective role in breast cancer patients.…”
Section: Pparγ As a Molecular Target For Breast Cancer Therapymentioning
confidence: 99%